Тaxation strategy for small businesses in the context of digitalization. - Verbivska Liudmyla, Liudmyla; Bak, Nataliia (Financial and Credit Activity: Problems of Theory and Practice, 2023)
The article examines the current problems of innovation, which in modern conditions acquire an important economic direction. The processesof globalization and digitization began in 2018 and continue to this day. These processes constantly affect all spheres of society, in particular the sphere of taxation. The article clarifies the main issues re-lated to the implementation and practical useof popular development trends and the improvement of innovative technology strategies in the process of taxation of small business entities in Ukraine. The key purpose of the study is the analysis of advanced strategies for the taxation of small business entities and their direct impact on the ac-counting and bookkeeping process in general. It was revealed that the main tasks of the research are as follows: the main requirements for the implementation of digitization in taxation are analyzed, the current state of taxation in Ukraine is considered, and we propose methods for the implementation and development of the accounting process at enterprises. This research is extremely insufficient in terms of theoretical and meth-odological aspects, the development ofthis issue and its growing practical importance. It is proven that the issue of taxation is being considered -the analysis of the effective-ness and necessity of digital technologies in tax accounting, the determination of their synthesis in auditing activities and the analysis of the prospects for the development of digital technologies in general. Ways of further development of the most effective tech-nologies are also described. The materials of foreign experts have been studied, which ensures the comprehensive importance of the implementation of digitalization of audit-ing activities in modern conditions.The conclusions of the study indicate the key strategies of taxation of small business entities, taking into account modern trends in this field. Information from the article can be used in the practice of improving the taxation process in Ukraine
Taxation strategy for small businesses in the context of digitalization. Financial and Credit Activity: Problems of Theory and Practice, 2023, 4(51), pp. 66–79
Keywords: economy, modernized technologies, digitalization of the taxation process, management solutions, digital transformation, accounting, enterprise, reporting, innovation, digital technologies